DEGRADASI SENYAWA PARAQUAT DALAM PESTISIDA GRAMOXONE® SECARA SONOZOLISIS DENGAN PENAMBAHAN TiO2-ANATASE - Neila Yenni; Safni Safni; Hamzar Suyani (Jurnal Riset Kimia, 2010)
ABSTRACT Degradation of Paraquat compound in Gramoxone pesticide had been done by sonolysis, ozonolysis, and sonozolysis. Sonolysis methods were performed using an ultrasound VC-1, ozonolysis using a bio-ozone space age sterilizer, and sonozolysis by combining sonolysis and ozonolysis methods. The optimum condition for degradation of 4 mg/L paraquat by sonolysis was found at temperature 40±1°C. Percentage of degradation at optimum condition was 22.80% with 90 minutes treatment. Whereas, with using ozonolysis method percentage of degradation of paraquat 4 mg/L was 50.39% with 60 minutes treatment. The combination of sonolysis and ozonolysis method simultaneously, these so-called sonozolysis, for degradation of the same compound, extend the percentage of degradation to 45.87% with only 30 minutes treatment. Keywords: Paraquat, Sonolisis, Ozonolisis